The Public and Private Management of Grief Recovering Normal - Pearce, Caroline; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Through a critical analysis of theory, policy and practice, The Public and Private Management of Grief looks at how 'recovery' is the prevailing discourse that measures and frames how people grieve, and considers what happens when people 'fail' to recover. Pearce draws on in-depth interviews with bereaved people and a range of bereavement professionals, to contemplate how 'failures' to recover are socially perceived and acted upon. Grounded in Foucauldian theory, this book problematises the notion of recovery, and instead argues for the acknowledgment of the experience of 'non-recovery,' highlighting how recovery is a socially and historically constructed notion linked to the individualised vision of health and happiness promoted by neo-liberal governmentality. This book will be of interest to students and scholars across sociology, anthropology, social work and psychology with a focus on death, dying and bereavement, grief studies, health and social care, as well as counsellors, clinical psychologists and social workers. .
1. Introduction: Recovering Normal -- 2. Grief as a Psychological Object of Study -- 3. Making Sense of Grief -- 4. Affective Practices: Managing Grief. - 5. Emotions, Bodies, Practices -- 6. Inhabiting and Resisting Identities. - 7. The Other Side of Recovery.
Keywords: Social medicine; Culture; Counseling; Community development; Social service; Medical Sociology; Sociology of Culture; Counseling Psychology; Social Work and Community Development